A market of black boxes: The political economy of Internet surveillance and censorship in Russia. Issue 1 (2nd January 2022) - Ermoshina, Ksenia; Loveluck, Benjamin; Musiani, Francesca
ABSTRACT: In recent years, the Russian Internet has developed according to strong centralizing and State-controlling tendencies, both in terms of legal instruments and technical infrastructure. This strategy implies a strong push to develop Russian-made technical solutions for censorship and traffic interception. Thus, a promising market has opened for Russian vendors of software and hardware solutions for traffic surveillance and filtering. Drawing from a mixed-methods approach and perspectives grounded primarily in Science and Technology Studies (STS), infrastructure studies and the political economy of information networks, this paper aims at exploring the flourishing sector of Russian industry of censorship and surveillance. We focus on two kinds of "black boxes" and examine their influence on the market of Internet Service Providers: surveillance systems known as SORM (System for Operative Investigative Activities), and traffic filtering solutions used to block access to websites that have been blacklisted by Roskomnadzor, the Russian federal watchdog for media and telecommunications. This research sheds light on the vivid debates around controversial technologies which Internet actors must adopt in order to avoid government fines, but which are expensive and complex to implement and raise a number of ethical and political concerns.